Business Plan : Online solar panel and batteries store in Ukraine - Golovin, Danylo; Pernica, Karel; Kubíček, Aleš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The main purpose of this thesis is to design and develop a business plan for launching an online store specializing in solar panels and batteries in Ukraine. The thesis is structured into two main parts: theoretical and practical. The theoretical part explores the key methods and tools required for creating an effective business plan, including PEST analysis, SWOT analysis, and the Business Model Canvas. In the practical part, these tools are applied to analyze the business environment, both external and internal. The plan further outlines a detailed marketing strategy and financial projections. The final findings confirm the business’s profitability and demonstrate that the concept is both feasible and sustainable.
Vedoucí práce: Karel Pernica
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses